PENGARUH KONSELING CALON PENGANTIN TERHADAP KEPATUHAN IBU DALAM MELAKUKAN PEMERIKSAAN KEHAMILAN SESUAI STANDAR DI PUSKESMAS BANGGAE I MAJENE - Nurul Annisa; Arfan Nur; Indah Tri Utami (Bina Generasi : Jurnal Kesehatan, 2023)
Interventions in reducing maternal mortality rates and infant mortality rates are not only carried out on pregnant women but must begin before pregnancy, namely on the prospective bride and groom by providing communication, information, education and reproductive health counseling as well as examinations for future bride and groom. Pre-marital counseling is a process of providing assistance by a professional to prospective husband and wife before carrying out marriage and providing provisions and instructions so that they can form a happy household life. The results of an initial study at Banggae 1 community Health centers on January-December 2022, 180 future bride and groom were counseled. Where among them who checked the pregnancy according to standards (KI) as many as 102 people, while the rest were not according to standards. This shows that there are still many future bride and groom who do not have standardized pregnancy checks. Based on these problems, the researcher is interested in examining how the influence of counseling of future bride and groom on mother's compliance in standardized prenatal checks. The purpose study is to determine the effect of counseling prospective brides on mother's compliance in standardized prenatal checks at Banggae 1 community Health centers. This study is quantitative method with a cross sectional study approach. It will be carried out in May 2023 with a population of 119 pregnant women who visited to Banggae 1 Majene Community Health Centers on January-April 2023 and sample of 54 people. The results showed that out of 54 respondents, 10 were in the category of respondents who did not receive counseling, while those who received counseling were 44 respondents. The conclusion is that there is an influence of prospective bride and groom counseling on mother's compliance in carrying out standard pregnancy checks at Banggae 1 Majene community Health centers.